Genderan Ada-Ada Ngobong Dupa Sumiyati Style | Genderan Ada-Ada Ngobong Dupa Gaya Sumiyati - Pembayun, Wahyu Thoyyib (GHURNITA: Jurnal Seni Karawitan, 2024)
This research is entitled "Genderan Ada-ada Ngobong Dupa Sumiyati Style". This research was motivated by researchers' admiration for the virtuosity and uniqueness of Sumiyati's style gender. The problem that will be elaborated in this study is how the techniques, patterns and dynamics used by Sumiyati in presenting genderan ada-ada Ngobong Dupa. The research method used is descriptive analysis. The analysis is carried out with several stages, namely: perceptive listening, participatory observation, transcription, identification of techniques, patterns, dynamics and drawing conclusions. Based on the analysis conducted, this research has obtained several findings regarding the technical elements, patterns, dynamics, and rhythms used by Sumiyati in presenting the ada-ada Ngobong Dupa. The technical elements that have been identified include cepengan, tutupan, and ukelan. The cepengan technique consists of the methit and sendhon techniques. The tutupan technique consists of balung, samparan, sarukan, lumpatan, umbaran, and pethetan. The ukelan technique consists of the two-tone and three-tone ukelan. The pattern elements that have been identified include kawitan, rambatan, seleh, oloran, and tutupan. The dynamic elements that have been identified include keras, sedheng, and lirih. The rhythmic elements that have been identified include seseg, sedheng, and tamban.